Re‐evaluation of the existing health‐based guidance values for copper and exposure assessment from all sources. (17th January 2023) - ,; More, Simon John; Bampidis, Vasileios; Benford, Diane; Bragard, Claude; Halldorsson, Thorhallur Ingi; Hernández‐Jerez, Antonio F; Bennekou, Susanne Hougaard; Koutsoumanis, Kostas; Lambré, Claude; Machera, Kyriaki; Mullins, Ewen; et al.
Abstract: Copper is an essential micronutrient and also a regulated product used in organic and in conventional farming pest management. Both deficiency and excessive exposure to copper can have adverse health effects. In this Scientific Opinion, the EFSA 2021 harmonised approach for establishing health‐based guidance values (HBGVs) for substances that are regulated products and also nutrients was used to resolve the divergent existing HBGVs for copper. The tightly regulated homeostasis prevents toxicity manifestation in the short term, but the development of chronic copper toxicity is dependent on copper homeostasis and its tissue retention. Evidence from Wilson disease suggests that hepatic retention is indicative of potential future and possibly sudden onset of copper toxicity under conditions of continuous intake. Hence, emphasis was placed on copper retention as an early marker of potential adverse effects. The relationships between (a) chronic copper exposure and its retention in the body, particularly the liver, and (b) hepatic copper concentrations and evidence of toxicity were examined. The Scientific Committee (SC) concludes that no retention of copper is expected to occur with intake of 5 mg/day and established an Acceptable Daily Intake (ADI) of 0.07 mg/kg bw. A refined dietary exposure assessment was performed, assessing contribution from dietary and non‐dietary sources. Background copper levels are a significant source of copper. The contribution of copper from its use as plant protection product (PPP), food and feed additives or fertilisers is negligible. The use of copper in fertilisers or PPPs contributes to copper accumulation in soil. Infant formula and follow‐on formula are important contributors to dietary exposure of copper in infants and toddlers. Contribution from non‐oral sources is negligible. Dietary exposure to total copper does not exceed the HBGV in adolescents, adults, elderly and the very elderly. Neither hepatic copper retention nor adverse effects are expected to occur from the estimated copper exposure in children due to higher nutrient requirements related to growth. Abstract : This publication is linked to the following EFSA Supporting Publications article: http://onlinelibrary.wiley.com/doi/10.2903/sp.efsa.2023.EN-7743/full